A free-standing, phase-change liquid metal mold for 3D flexible microfluidics - Yan, Sheng; Yuan, Qingwei; Wu, Jialin; Jia, Zixuan (Frontiers in Bioengineering and Biotechnology, 2022)
This paper describes a method to fabricate the 3D microfluidic channel using the free-standing, phase-change gallium mold. Three approaches to prepare the free-standing gallium molds are described. The solid metal framework is strong enough to stand against the gravity. After casting, the embedded gallium molds are melted from solid to liquid and then extracted from the encasing elastomer to form the 3D microfluidic channel due to the phase change property. Since this method is compatible with many encasing materials (e.g., elastomers, gels, resins, ceramics), the encasing materials will bring novel functionalities to the microfluidic chip. Two proof-of-concept experiments have been demonstrated. Firstly, a soft, sticky, on-skin microfluidic cooler is developed based on this method to deliver the focused, minimal invasive cooling power at arbitrary skins of human body with temperature control. Secondly, an ultra-stretchable viscoelastic microchannel with the ultra-soft base is fabricated to continuously tune the viscoelastic particle focusing with a large dynamic range. This proposed technique suggests the new possibilities for the development of lab-on-a-chip applications.